A new HPLC method for simultaneously measuring chloride, sugars, organic acids and alcohols in food samples - Zaky, Abdelrahman Saleh; Pensupa, Nattha; Andrade-Eiroa, Áurea; Tucker, Gregory A.; Du, Chenyu (Elsevier, 2017)
This paper introduces an original, rapid, efficient and reliable HPLC method for the accurate and simultaneous quantification (g/L) of chloride in samples containing sugars, organic acids and alcohols. Separation was achieved using a HI-Plex H column at 35oC, with H2SO4 (0.005 N) as the mobile phase at a flow rate of 0.4 mL/min. The column effluent was monitored by a Refractive Index (RI) detector. A linear response was achieved over NaCl concentrations of 0.25 – 2.5 g/L and 5 – 40 g/L. The analytical method inter- and intra-run accuracy and precision were better than ±10.0%. Investigating the mechanism of detection using different chloride and sodium s reviled that this method can be used for determining the total concentration of chloride salts when in suspension. This method was successfully applied to 15 samples of commercial food products and the salt content obtained from this method was compared with 3 other methods for salt determination. The (HI-Plex H) column was designed for determining the concentrations of sugars, organic acids and alcohols when in solution. Hence, application of our new methodology would allow the determination of sugars, alcohols and organic acids in samples derived from seawater-based fermentation media as well as samples from salty food and dairy products.